Host A-to-I RNA editing signatures in intracellular bacterial and single-strand RNA viral infections - Wei, Zhi-Yuan; Wang, Zhi-Xin; Li, Jia-Huan; Wen, Yan-Shuo; Gao, Di; Xia, Shou-Yue; Li, Yu-Ning; Pan, Xu-Bin; Liu, Yan-Shan; Jin, Yun-Yun; Chen, Jian-Huan (Frontiers in Immunology, 2023)
Background: Microbial infection is accompanied by remodeling of the host transcriptome. Involvement of A-to-I RNA editing has been reported during viral infection but remains to be elucidated during intracellular bacterial infection. Results: Herein we analyzed A-to-I RNA editing during intracellular bacterial infections based on 18 RNA-Seq datasets of 165 infected mice samples involving 7 tissue types and 8 intracellular bacterial pathogens (IBPs), and identified a consensus signature of RNA editing for IBPs infections, mainly involving neutrophil-mediated innate immunity and lipid metabolism. Further comparison of patterns of host RNA editing revealed remarkable similarities between pneumonia caused by IBPs and single-strand RNA (ssRNA) viruses, such as altered expression of editing enzymes, editing site number, and editing level. In addition, functional enrichment analysis of gene with RNA editing highlighted that the Rab GTPase family plays a common and vital role in the host immune response to the infection of both IBPs and ssRNA viruses, which was typically represented by the consistent up-regulated RNA editing of Ras-related proteins 27a (Rab27a). Nevertheless, dramatic differences between infection of IBPs and viruses were also observed, and clearly distinguished the two types of intracellular infection. Conclusion: Our study showed transcriptome-wide host A-to-I RNA editing alteration during infections by IBPs and ssRNA viruses. By identifying and comparing consensus signatures of host A-to-I RNA editing in the lung, our analysis implicates the importance of host A-to-I RNA editing during IBPs infections and provides new insights into the diagnosis and treatment of infectious diseases.